Local economic benefits of ecotourism development in Malaysia: the case of Redang Island Marine Park - Yacob, Mohd Rusli; Shuib, Ahmad; Mamat, Mohd Farid; Radam, Alias (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
This paper is an empirical study of the local economic benefits of ecotourism development in one of the marine parks in Malaysia. The Redang Island Marine Park (RIMP) was selected as a case study in order to estimate local economic benefits in terms of employment opportunities provided by the ecotourism sector and other related sectors. Sixteen ecotourism operators were interviewed to elicit financial information while 82 employees involved in the ecotourism sector were also interviewed in order to determine expenditure patterns. The results showed that the development of ecotourism in RIMP has definitely generated local employment opportunities. A total of 938 jobs were created which included direct, indirect and induced employment. The output multiplier was very small compared to the employment multipliers which were 1.104 and 1.223 respectively. The high percentage of leakages in the expenditures of ecotourism operators and their employees had contributed to the low multiplier effects.